Refractive Error and the Risk of Age-Related Macular Degeneration in the South Korean Population. Issue 2 (March 2016) - Lin, Shuai-Chun; Singh, Kuldev; Chao, Daniel L.; Lin, Shan C.
Abstract : Purpose: We investigated the association between refractive error and the prevalence of age-related macular degeneration (AMD) in a population-based study. Design: This was a cross-sectional study. Methods: Right eyes were included from 14, 067 participants aged 40 years and older with gradable fundus photographs and refraction data from the fourth and the fifth Korea National Health and Nutrition Examination Survey 2008 to 2011. Early and late AMD was graded based on the International Age-Related Maculopathy Epidemiological Study Group grading system. Autorefraction data were collected to calculate spherical equivalent refraction in diopters (D) and classified into 4 groups: hyperopia (≥1.0 D), emmetropia (−0.99 to 0.99 D), mild myopia (−1.0 to −2.99 D), and moderate to high myopia (⩽−3.0 D). Results: After adjustment for potential confounders, each diopter increase in spherical equivalent was associated with a 16% [odds ratio (OR), 1.16; 95% confidence interval (CI), 1.08–1.25] and 18% (OR, 1.18; 95% CI, 1.10–1.27) increased risk of any (early + late) and early AMD, respectively. Mild and moderate to high myopia were associated with lower odds of any and early AMD compared with hyperopia (any AMD: OR, 0.62; 95% CI, 0.4–0.95 for mild myopia; OR, 0.41; 95% CI, 0.21–0.81 for moderate to high myopia; early AMD: OR, 0.63; 95% CI, 0.4–0.99 for mild myopia; OR, 0.36; 95% CI, 0.16–0.77 for moderate to high myopia group). There was no association between refractive status and the likelihood of late AMD ( P = 0.91). Conclusions: Myopia is associated with lower odds of any and early AMD, but not with late AMD in the South Korean population.